2017
DOI: 10.1111/cas.13350
|View full text |Cite
|
Sign up to set email alerts
|

Mutation status of RAD51C,PALB2 and BRIP1 in 100 Japanese familial breast cancer cases without BRCA1 and BRCA2 mutations

Abstract: In addition to BRCA1 and BRCA2, RAD51C,PALB2 and BRIP1 are known as breast cancer susceptibility genes. However, the mutation status of these genes in Japanese familial breast cancer cases has not yet been evaluated. To this end, we analyzed the exon sequence and genomic rearrangement of RAD51C,PALB2 and BRIP1 in 100 Japanese patients diagnosed with familial breast and ovarian cancer and without BRCA1 and BRCA2 mutations. We detected a large deletion from exons 6 to 9 in RAD51C, 4 novel BRIP1 missense variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(133 reference statements)
0
7
0
2
Order By: Relevance
“…Accumulating evidence indicates that patients with BRIP1 mutations have HRR deficiency and are consequently hypersensitive to PARP inhibition. 14 BRIP1 is a BRCA1-interacting protein (the BRIP1-BRCA1 interaction is important for HRR) and associates with BRCA1 as cells progress through the S phase of the cell cycle. 15 , 16 BRIP1 is a DNA helicase that interacts with the COOH-terminal BRCT repeat of BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that patients with BRIP1 mutations have HRR deficiency and are consequently hypersensitive to PARP inhibition. 14 BRIP1 is a BRCA1-interacting protein (the BRIP1-BRCA1 interaction is important for HRR) and associates with BRCA1 as cells progress through the S phase of the cell cycle. 15 , 16 BRIP1 is a DNA helicase that interacts with the COOH-terminal BRCT repeat of BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…Also mutations in RAD51C have not been found to increase the risk of breast cancer [ 18 20 ] and mutations in RAD51D have been associated with high risk of ovarian cancer but not with breast cancer [ 21 ]. Nevertheless, other studies have indicated that mutations in RAD51C [ 22 ] and RAD51D [ 17 , 23 , 24 ] contribute to the risk of both breast and ovarian cancer, and that RAD50 is an intermediate-risk breast cancer susceptibility gene [ 25 ]. Although germline mutations in the DNA mismatch repair genes ( MLH1, MSH2, MSH6, PMS2 ) have been mostly associated with Lynch syndrome, evidence has been established to support the connections between the mutations in the DNA mismatch repair genes and the risk or survival of breast cancer [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although germline mutations in the DNA mismatch repair genes ( MLH1, MSH2, MSH6, PMS2 ) have been mostly associated with Lynch syndrome, evidence has been established to support the connections between the mutations in the DNA mismatch repair genes and the risk or survival of breast cancer [ 26 29 ]. Similarly, whether BRIP1 is a breast cancer susceptibility gene remains controversial [ 30 ], and perhaps is dependent on the ethnicity of the cohort studied [ 22 ]. NF1 mutations have been known to associate with increased risk of breast cancer in younger population [ 31 ] and poor breast cancer survival [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…U nosiček mutace genu RAD51C by ale měla být zvážena preventivní adnexektomie ve 45-50 le tech (event. dříve, věk posuzovat podle nejčasnějšího výskytu karcinomu ovaria v rodině, podobně jako u nosiček mu tace genu BRIP1) [18,20,22,23].…”
Section: Nbnunclassified
“…Souvislost mutací genu BRIP1 se zvýšeným rizikem karci nomu prsu nebyla jednoznačně proká zána, i když je v ně kte rých publikacích možná souvislost uváděna vč. databází OMIM a ClinVar [21][22][23].…”
Section: Nbnunclassified